Analisis Hambatan Samping Terhadap Kinerja Ruas Jalan HR Soebrantas Kota Pekanbaru - Sonya Elva Devera; Winayati Winayati; Hendri Rahmat (Universitas Lancang Kuning, 2023)
Based on the initial survey on HR Soebrantas Road, it is also often found that there are many street vendors selling on the shoulder of the road, namely STA 1+300 – STA 1+900. This activity will certainly increase the volume of congestion caused by the large number of merchandise buyers who stop on the road. The purpose of this study was to analyze the side barriers and vehicle volume on the performance of HR Soebrantas Road, Pekanbaru City. Calculation of road capacity using the 1997 MKJI method. After calculating the traffic volume, the highest volume was found on Friday, 29 April 2022 at 17.00 – 18.00 at 1.115 Smp/hour/direction so that the capacity of the road with side barriers was 1.334 Smp/hour/ direction. The highest side resistance value is 1.144 events/hour, therefore the degree of saturation is 0,835 and the service level value is in class D approaching unstable current and low speed. Meanwhile, the speed of vehicles on HR Soebrantas Road, due to side obstacles for motorbikes is 48,40 km/hour (MC), for light vehicles it is 44,66 km/hour (LV) and for medium heavy vehicles it is 40,83 km/hour (HV).